F**k Flying : 101 eco-friendly ways to travel - Orion Publishing Group (London : Trapeze, 2020)
This book will show you all the ways YOU can change how you travel to help save the planet. As we come out of lockdown, many of us are thinking about getting out of the house and going on holiday but it's never been more important to think about how we get from A to B. Packed with 101 tips and tricks to reducing your carbon footprint when you're on the go, this practical little book shows that everybody can do something to protect our environment. From how you travel to work, head to the shops, go on holiday and more, this book is a must-read for everyone.
Keywords: Ecotoerisme; Luchtvaart; Reizen; Toerisme